The persistence of entrepreneurship myths - Bridge, Simon (New York, NY : Routledge, 2022)
"Triggered largely by claims that small businesses were the main source of new jobs, an 'explosion' of interest in enterprise, entrepreneurs and small business has led to the establishment of a conventional wisdom about enterprise. Mistaken theories can become influential and examining the conventional enterprise wisdom indicates that much of it is questionable. If that is the case, a reassessment is needed. While wilful blindness and continuing to do more of the same is a natural response, it will not lead to improvements in knowledge. A new paradigm requires a step change in thinking, which is not easy to initiate. Nevertheless, accepting the evidence for the errors in current understanding and practice is a necessary first step if enterprise and its benefits are to be better understood and promoted. This book examines the conventional wisdom around enterprise, entrepreneurs and small businesses and illustrates not only why and how this could have evolved, but also why it could be based on a set of mistaken assumptions. Correcting the foundational knowledge on which enterprise and policy and practice rely and finding a new paradigm will result in better teaching and more effective policy. It will therefore be of interest to researchers, academics, students and policy makers in the fields of enterprise and entrepreneurship"--
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship; Small business; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Small Business; BUSINESS & ECONOMICS / Corporate & Business History